Acculturation of Islam And Local Culture in Acehnese Traditional Traditions: A Study On Peusijuek Haji - Ash shifa Annur; Inayatillah, Inayatillah (FITRAH: International Islamic Education Journal, 2025)
This study explores the acculturation between Islam and local Acehnese culture within the Peusijuek Haji tradition, a customary ritual performed before departure or upon the return of pilgrims from the Hajj. This tradition represents the convergence of two sacred dimensions, religious and cultural, reflecting the Islamization of local symbols through a reinterpretation of their spiritual meanings. The research aims to describe the forms of Islamic and local cultural acculturation within Peusijuek Haji and to explain its philosophical meanings and socio-religious functions for Acehnese society. The study employs a descriptive qualitative method using a library research approach, analyzing literature, customary archives, and local documentation. The findings indicate that acculturation occurs through symbolic and social transformation: traditional elements such as rice (breuh padee), ceremonial flour (teupong taweu), and leaves (on sisijeuk) are redefined as symbols of purification and blessings consistent with Islamic teachings. Furthermore, a dialogical dynamic among religious scholars, customary leaders, and pilgrim families shapes ritual practices that harmonize with Islamic law while preserving cultural values. Variations across generations and regions reveal that Peusijuek Haji represents a selective form of acculturation, demonstrating the Acehnese community's ability to maintain a balance between tradition and religion. This study concludes that Peusijuek Haji functions not only as a religious symbol but also as a means of strengthening social solidarity and Acehnese cultural identity.